2023
DOI: 10.1021/acs.energyfuels.3c02754
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals, Applications, and Perspectives of Liquid Metals in Catalysis: An Overview of Molecular Simulations

Xing Zhi,
Fangxi Xie,
Ali Zavabeti
et al.

Abstract: The liquid metal catalysts present catalytic systems with dynamic interfaces and mobile active atoms. The origin of catalytic performance in such a liquid phase system has remained elusive for the rational design of efficient liquid metal catalysts. A detailed understanding of the atomistic structure and fundamental chemistry at the interface of liquid metals would optimize materials for catalytic reactions. However, there has been limited success in fully addressing the atomic-level structural arrays of liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…The review includes transition metal decoration, heteroatom doping, and multi-heteroatom co-doping methods of the carbon-based catalysts. Zhi et al reviewed comprehensively the development of liquid metals as catalysts with advantageous characteristics for a wide range of applications (such as thermocatalytic H 2 production, methanol synthesis, etc.). This review explores the fundamental properties and reaction chemistry of liquid metal catalysts.…”
Section: Other Topicsmentioning
confidence: 99%
“…The review includes transition metal decoration, heteroatom doping, and multi-heteroatom co-doping methods of the carbon-based catalysts. Zhi et al reviewed comprehensively the development of liquid metals as catalysts with advantageous characteristics for a wide range of applications (such as thermocatalytic H 2 production, methanol synthesis, etc.). This review explores the fundamental properties and reaction chemistry of liquid metal catalysts.…”
Section: Other Topicsmentioning
confidence: 99%
“…In comparison to organic solvents, liquid metals (LMs) can be used with fewer temperature limitations. A LM is a rapidly developing area for different applications. Low melting point, easy recovery, high mobility, and high surface energy are the main advantages of LM for catalysis. It is reported that bimetallic catalysts based on supported Ni, Pd, and Pt promoted with Ga have demonstrated high selectivity, activity, and stability in hydrogenation and dehydrogenation reactions. The reaction proceeds on the intermetallic surface with modification of the electronic structure and isolation of the metal active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Post-transition metal cations, including Pb 2+ , Sn 2+ , Bi 3+ , and Sb 3+ , have a wide variety of applications in electrochemical energy storage [1,2] high-temperature superconductivity [3][4][5], catalysis [5][6][7], gas sensors [8][9][10], birefringent material [11][12][13][14], nonlinear optical crystals [15][16][17][18], etc. By analyzing many existing studies, it was found that the introduction of post-transition metal cations containing stereochemically active lone-pair electrons is a good strategy to enhance optical properties.…”
Section: Introductionmentioning
confidence: 99%